Effect of nanosepiolite and nanosilica content, polyethylene-grafted-maleic anhydride and irganox 1010 on tensile and morphological of low density polyethylene nanocomposites - Nadia Husna Mohamad Saleh (School of Materials Engineering, Universiti Malaysia Perlis, 2017)
The main goal of this study is to evaluate the effectiveness of developing a high durability greenhouse plastic cover by incorporating nanosepiolite and nanosepiolite and nanosilica as reinforced filler. The specific objectives are ; to study the effect of nanosepiolite and nanosilica content on the mechanical and morphology properties of LDPE/nanocomposites ; to compare the mechanical properties, morphology, FTIR analysis and ageing of LDPE/nanosepiolite and LDPE/nanosilica ; to investigate the effect of MAPE to properties of LDPE nanocomposites ; to analyze the effect of Irganox 1010 content on thermal ageing of LDPE nanocomposites.